Analisis Geometri Lereng Pada Ruas Jalan Sicincin-Malalak KM 33 Kecamatan Malalak Kabupaten Agam Provinsi Sumatera Barat - Welly Handa Nuraga; Raimon Kopa; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2018)
The slope geometry stability on the Sicincin-Malalak road section on KM 33 was analyzed using the limit equilibrium method by using mining software and then manually calculating the slope safety using the Fellenius method and testing using Hoek and Bray diagrams (1981). Type of the failure on the hill in KM 33 was an arc landslide (circular failure) because the landslide on the slope forms is a semicircle. Determination of the safe or not slope in the study location is guided by the Decree of the Minister of Public Works in 1987. Who proposes the road slope can be declared safe if it has a slope safety value without an earthquake above 1.35. As for conditions with earthquakes, the safety value of the slope must be above 1.2. Trial slope testing at the study site was carried out by slope slope every 5 ° from the slope of the 49 ° slope. The slope is then assumed under various conditions, it was dry, natural, saturated, and earthquake for slope of 44 °, 39 ° and 34 °. After analyzing and calculations using various methods, the slope with a 34 ° slope is a recommendation because it has a security value above 1.35 for conditions without earthquakes, the slope length is 31.625 m and the slope is declared safe. The results of the tests are expected to be recommendations for preventing landslides.Keywords: Slope Stability, Safety Factor, Circular Failure, Mining Software, Fellenius Method, Hoek and Bray Method